Tinjauan terhadap UU ITE untuk Penerapan Rekam Medis Berbasis Online pada Penduduk Muslim di Indonesia - Nynda Fatmawati Octarina; Muh. Barid Nizaruddin Wajdi; M. Ikhsan Setiawan; Agus Sukoco; Tubagus Purworusmiardi; Nuning Kurniasih (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2017)
As the largest Muslim country in the world, Indonesia must have a complete analysis documents of medical records on online-based. especially for the Muslim population in Indonesia. Currently, Indonesia does not have laws specifically regulate the electronic medical records. Therefore, violation of the protection of personal data in electronic medical records may refers to any one part of the private right as set forth in the elucidation of 26th article 1st verse of UU ITE.